Activists, alliances, and anti-U.S. base protests - Yeo, Andrew, 1978- (Cambridge studies in contentious politics., 2011)
"No other country maintains a global military presence comparable to the United States. Yet outside the United States, considerable debate exists about what this presence is about and how well it serves national and global interests. Anti-U.S. base protests, played out in parliaments and the streets of host nations, continue to arise in different parts of the world. In a novel approach fusing international relations theory with social movement perspectives, this book examines the impact of anti-base movements and the important role bilateral alliance relationships play in shaping movement outcomes. The author explains not only when and how anti-base movements matter, but also how host governments balance between domestic and international pressure on base-related issues. Drawing on interviews with activists, politicians, policy makers, and U.S. base officials in the Philippines, Japan (Okinawa), Ecuador, Italy, and South Korea, the author finds that the security and foreign policy ideas held by host government elites act as a political opportunity or barrier for anti-base movements, influencing their ability to challenge overseas U.S. basing policies"--